Slow down of charge transfer owing to auger recombination and two-photon action cross-section of CdS–CdSe–CdS segmented nanorods - Subha, Radhu (2015)
We report on the dynamical properties of photoexcited carriers, particularly the charge transfer, in CdS–CdSe–CdS segmented nanorods using femtosecond transient pump–probe spectroscopy. Design of this kind of heteronanostructures with the possibility of variation of the relative volumes of CdS and CdSe segments permits independent tuning of one-photon and two-photon absorption cross-sections over a wide range of wavelengths, with specific advantages in applications related to photovoltaics and multiphoton microscopy. Intensity-dependent charge transfer dynamics in CdS–CdSe–CdS segmented nanorods indicates that the rate of charge transfer from CdS to CdSe is influenced by the number of electron–hole pairs generated in the nanorod. We attribute this change in the rate constant to Auger recombination-assisted charge transfer, which becomes the predominant relaxation mechanism at high intensities. Charge transfer also results in a large two-photon absorption cross-section, on the order of 104 GM (1 GM = 10–50 cm4 s photon–1), at 1.55 eV in these heteronanostructures. Furthermore, two-photon absorption induced photoluminescence on near-infrared excitation (1.55–0.99 eV) suggests that the local field effects plays a role in determining the effective two-photon action cross-section of heteronanostructures, offering a platform for engineering optical nonlinearity.